Atmospheric photochemistry of aromatic hydrocarbons: OH budgets during SAPHIR chamber experiments - S. Nehr; B. Bohn; H.-P. Dorn; H. Fuchs; R. Häseler; A. Hofzumahaus; X. Li; F. Rohrer; R. Tillmann; A. Wahner (Atmospheric Chemistry and Physics, 2014)
Current photochemical models developed to simulate the atmospheric degradation of aromatic hydrocarbons tend to underestimate OH radical concentrations. In order to analyse OH budgets, we performed experiments with benzene, toluene, p-xylene and 1,3,5-trimethylbenzene in the atmosphere simulation chamber SAPHIR. Experiments were conducted under low-NO conditions (typically 0.1–0.2 ppb) and high-NO conditions (typically 7–8 ppb), and starting concentrations of 6–250 ppb of aromatics, dependent on OH rate constants. For the OH budget analysis a steady-state approach was applied in which OH production and destruction rates (POH and DOH) have to be equal. The POH were determined from measurements of HO2, NO, HONO, and O3 concentrations, considering OH formation by photolysis and recycling from HO2. The DOH were calculated from measurements of the OH concentrations and total OH reactivities. The OH budgets were determined from DOH/POH ratios. The accuracy and reproducibility of the approach were assessed in several experiments using CO as a reference compound where an average ratio DOH/POH = 1.13 ± 0.19 was obtained. In experiments with aromatics, these ratios ranged within 1.1–1.6 under low-NO conditions and 0.9–1.2 under high-NO conditions. The results indicate that OH budgets during photo-oxidation experiments with aromatics are balanced within experimental accuracies. Inclusion of a further, recently proposed OH production via HO2 + RO2 reactions led to improvements under low-NO conditions but the differences were small and insignificant within the experimental errors.